Pengaruh Model Pembelajaran Kooperatif tipe Team Games Tournament (TGT) pada Mata Pembelajaran IPAS untuk Meningkatkan Keterampilan Sosial: Siswa Kelas IV SDN X - Leli Syafitri; Dodik Kariadi (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study aims to determine: 1) whether there are differences in social skills before and after the implementation of the Team Games Tournament (TGT) cooperative learning model and the direct learning model in the science subject for fourth-grade students of SDN X; and 2) how much influence the use of the TGT cooperative learning model has on students' social skills. The background of this study is based on the importance of developing social skills from an early age, especially through a collaborative learning approach that encourages active interaction between students. Social skills are considered essential for students to build collaboration, responsibility, and tolerance in classroom settings. The method used in this study is a quantitative approach with a quasi-experimental design. The research sample consisted of fourth-grade students who were divided into two groups, namely the experimental class that implemented the TGT model and the control class that used direct learning. The research instrument was a social skills test sheet with four main indicators, namely cooperation, communication, responsibility, and tolerance. The cooperative learning model provides opportunities for students to learn not only academically but also socially through structured interaction. The results of the study showed a significant difference in the improvement of social skills between the experimental and control groups. Students in the experimental group experienced greater improvement in social skills, particularly in cooperation and communication. The TGT model has been proven to create a fun learning atmosphere, foster healthy competition, and encourage students to be more active in discussions and group activities. This finding confirms that TGT can be an effective strategy to improve students' social competence in elementary schools. Therefore, it can be concluded that the TGT cooperative learning model has a positive influence on improving students' social skills. This study recommends implementing TGT as an alternative effective learning strategy in science subjects in elementary schools.